The microbial ecology of a Mediterranean chlorinated drinking water distribution systems in the city of Valencia (Spain) - Del Olmo, Gonzalo; Husband, Stewart; Sánchez Briones, Carmen; Soriano, Adela; Calero Preciado, Carolina; Macian, Javier; Douterelo, Isabel (The Science of the total environment, 2021)
Drinking water distribution systems host extensive microbiomes with diverse biofilm communities regardless of treatment, disinfection, or operational practices. In Mediterranean countries higher temperatures can accelerate reactions and microbial growth that may increase aesthetic water quality issues, particularly where material deposits can develop as a result of net zero flows within looped urban networks. This study investigated the use of flow and turbidity monitoring to hydraulically manage mobilisation of pipe wall biofilms and associated material from the Mediterranean city of Valencia (Spain). Pipe sections of different properties were subjected to controlled incremental flushing with monitoring and sample collection for physico-chemical and DNA analysis with Illumina sequencing of bacterial and fungal communities. A core microbial community was detected throughout the network with microorganisms like Pseudomonas, Aspergillus or Alternaria increasing during flushing, indicating greater abundance in underlying and more consolidated material layers. Bacterial and fungal communities were found to be highly correlated, with bacteria more diverse and dynamic during flushing whilst fungi were more dominant and less variable between sampling sites. Results highlight that water quality management can be achieved through hydraulic strategies yet understanding community dynamics, including the fungal component, will be key to maintaining safe and ultimately beneficial microbiomes in drinking water distribution systems. [Display omitted] •Monitoring turbidity during flushing allows network performance analysis.•Hydraulic strategies can be applied to control water quality issues from biofilms.•Controlled flushing facilitated network and pipe biofilm community analysis.•Core-community of microorganisms were present throughout the network.•Bacteria showed more diversity with fungi more dominant and stable.